Feeding styles and child weight status among recent immigrant mother-child dyads - Tovar Alison; Hennessy Erin; Pirie Alex; Must Aviva; Gute David M; Hyatt Raymond R; Kamins Christina; Hughes Sheryl O; Boulos Rebecca; Sliwa Sarah; Galvão Heloisa; Economos Christina D (BMC, 2012)
Abstract Background Research has shown that parental feeding styles may influence children's food consumption, energy intake, and ultimately, weight status. We examine this relationship, among recent immigrants to the US. Given that immigrant parents and children are at greater risk for becoming overweight/obese with increased time in the US, identification of risk factors for weight gain is critical. Methods Baseline data was collected on 383 mother-child dyads enrolled in Live Well, a community-based, participatory, randomized controlled lifestyle intervention to prevent weight gain in recent immigrant mothers. Socio-demographic information together with heights and weights were collected for both mother and child. Acculturation, behavioral data, and responses to the Caregiver's Feeding Styles Questionnaire (CFSQ) were also obtained from the mother. Results The children's average age was 6.2 ± 2.7 years, 58% male. Mothers had been in the country for an average of 6.0 ± 3.3 years, and are Brazilian (36%), Haitian (34%) and Latino (30%). Seventy-two percent of the mothers were overweight/obese, while 43% of the children were overweight/obese. Fifteen percent of mothers reported their feeding style as being high demanding/high responsive; 32% as being high demanding/low responsive; 34% as being low demanding/high responsive and 18% as being low demanding/low responsive. In bivariate analyses, feeding styles significantly differed by child BMIz-score, ethnic group, and mother's perceived stress. In multiple linear regression, a low demanding/high responsive feeding style was found to be positively associated (ß = 0.56) with a higher child weight as compared to high demanding/high responsive, controlling for known covariates (p = 0.01). Conclusions Most mothers report having a low demanding/high responsive feeding style, which is associated with higher child weight status in this diverse immigrant population. This finding adds to the growing literature that suggests this type of feeding style may be a risk factor for childhood obesity. Further research is needed to help understand the larger socio-cultural context and its influence on feeding dynamics among immigrant families and families of lower incomes. How parents establish a certain feeding style in their home country compared to when they move to the US "obesogenic" environment, should also be explored.